ANALISIS PERATURAN PENGEMBALIAN BARANG BUKTI YANG TIDAK SESUAI DENGAN KEADAAN AWAL WAKTU PENYITAAN - Susilo, Agung Hendro; astuti, pudji (NOVUM : JURNAL HUKUM, 2021)
Abstract Handling of confiscated evidence is guided by the law number 8 of 1981 concerning the criminal procedure code and the regulation of the minister of environment and forestry number. P.26/Menlhk/Setjen/Kum.1/4/2017 concerning the handling of evidence of environmental and forestry crime. The two rules do not mention "Evidence" clearly. The purpose of this study is to analyze the legal regulations on the return of evidence at the initial time of confiscation so that it shows the suitability of criminal law enforcement actions with the laws that govern it, to find out the responsibility of law enforcement officers for the damage of confiscated evidence so that it is proven as a confiscation error in the criminal law enforcement process.This research is a type of normative or doctrinal legal research to examine the issue of the rule of law in the return of evidence in the form of protected protected birds whose species and numbers are reduced due to the death of the protected animal in the process of handling evidence that has not yet been found to be legal. Errors in handling evidence that result in a mismatch of returning evidence with the initial state of confiscation are reviewed from the principle of legal justice based on existing legal regulations. Keywords : Evidence, legal vacuum, Regulatory Analysis, Criminal Acts, Legal Certainty.